Case-finding and improving patient outcomes for chronic obstructive pulmonary disease in primary care: the BLISS research programme including cluster RCT - Peymané Adab (NIHR Journals Library, 2021)
Background: Chronic obstructive pulmonary disease is a major contributor to morbidity, mortality and health service costs but is vastly underdiagnosed. Evidence on screening and how best to approach this is not clear. There are also uncertainties around the natural history (prognosis) of chronic obstructive pulmonary disease and how it impacts on work performance. Objectives: Work package 1: to evaluate alternative methods of screening for undiagnosed chronic obstructive pulmonary disease in primary care, with clinical effectiveness and cost-effectiveness analyses and an economic model of a routine screening programme. Work package 2: to recruit a primary care chronic obstructive pulmonary disease cohort, develop a prognostic model [Birmingham Lung Improvement StudieS (BLISS)] to predict risk of respiratory hospital admissions, validate an existing model to predict mortality risk, address some uncertainties about natural history and explore the potential for a home exercise intervention. Work package 3: to identify which factors are associated with employment, absenteeism, presenteeism (working while unwell) and evaluate the feasibility of offering formal occupational health assessment to improve work performance. Design: Work package 1: a cluster randomised controlled trial with household-level randomised comparison of two alternative case-finding approaches in the intervention arm. Work package 2: cohort study – focus groups. Work package 3: subcohort – feasibility study. Setting: Primary care settings in West Midlands, UK. Participants: Work package 1: 74,818 people who have smoked aged 40–79 years without a previous chronic obstructive pulmonary disease diagnosis from 54 general practices. Work package 2: 741 patients with previously diagnosed chronic obstructive pulmonary disease from 71 practices and participants from the work package 1 randomised controlled trial. Twenty-six patients took part in focus groups. Work package 3: occupational subcohort with 248 patients in paid employment at baseline. Thirty-five patients took part in an occupational health intervention feasibility study. Interventions: Work package 1: targeted case-finding – symptom screening questionnaire, administered opportunistically or additionally by post, followed by diagnostic post-bronchodilator spirometry. The comparator was routine care. Work package 2: twenty-three candidate variables selected from literature and expert reviews. Work package 3: sociodemographic, clinical and occupational characteristics; occupational health assessment and recommendations. Main outcome measures: Work package 1: yield (screen-detected chronic obstructive pulmonary disease) and cost-effectiveness of case-finding; effectiveness of screening on respiratory hospitalisation and mortality after approximately 4 years. Work package 2: respiratory hospitalisation within 2 years, and barriers to and facilitators of physical activity. Work package 3: work performance – feasibility and acceptability of the occupational health intervention and study processes. Results: Work package 1: targeted case-finding resulted in greater yield of previously undiagnosed chronic obstructive pulmonary disease than routine care at 1 year [n = 1278 (4%) vs. n = 337 (1%), respectively; adjusted odds ratio 7.45, 95% confidence interval 4.80 to 11.55], and a model-based estimate of a regular screening programme suggested an incremental cost-effectiveness ratio of £16,596 per additional quality-adjusted life-year gained. However, long-term follow-up of the trial showed that at ≈4 years there was no clear evidence that case-finding, compared with routine practice, was effective in reducing respiratory admissions (adjusted hazard ratio 1.04, 95% confidence interval 0.73 to1.47) or mortality (hazard ratio 1.15, 95% confidence interval 0.82 to 1.61). Work package 2: 2305 patients, comprising 1564 with previously diagnosed chronic obstructive pulmonary disease and 741 work package 1 participants (330 with and 411 without obstruction), were recruited. The BLISS prognostic model among cohort participants with confirmed airflow obstruction (n = 1894) included 6 of 23 candidate variables (i.e. age, Chronic Obstructive Pulmonary Disease Assessment Test score, 12-month respiratory admissions, body mass index, diabetes and forced expiratory volume in 1 second percentage predicted). After internal validation and adjustment (uniform shrinkage factor 0.87, 95% confidence interval 0.72 to 1.02), the model discriminated well in predicting 2-year respiratory hospital admissions (c-statistic 0.75, 95% confidence interval 0.72 to 0.79). In focus groups, physical activity engagement was related to self-efficacy and symptom severity. Work package 3: in the occupational subcohort, increasing dyspnoea and exposure to inhaled irritants were associated with lower work productivity at baseline. Longitudinally, increasing exacerbations and worsening symptoms, but not a decline in airflow obstruction, were associated with absenteeism and presenteeism. The acceptability of the occupational health intervention was low, leading to low uptake and low implementation of recommendations and making a full trial unfeasible. Limitations: Work package 1: even with the most intensive approach, only 38% of patients responded to the case-finding invitation. Management of case-found patients with chronic obstructive pulmonary disease in primary care was generally poor, limiting interpretation of the long-term effectiveness of case-finding on clinical outcomes. Work package 2: the components of the BLISS model may not always be routinely available and calculation of the score requires a computerised system. Work package 3: relatively few cohort participants were in paid employment at baseline, limiting the interpretation of predictors of lower work productivity. Conclusions: This programme has addressed some of the major uncertainties around screening for undiagnosed chronic obstructive pulmonary disease and has resulted in the development of a novel, accurate model for predicting respiratory hospitalisation in people with chronic obstructive pulmonary disease and the inception of a primary care chronic obstructive pulmonary disease cohort for longer-term follow-up. We have also identified factors that may affect work productivity in people with chronic obstructive pulmonary disease as potential targets for future intervention. Future work: We plan to obtain data for longer-term follow-up of trial participants at 10 years. The BLISS model needs to be externally validated. Our primary care chronic obstructive pulmonary disease cohort is a unique resource for addressing further questions to better understand the prognosis of chronic obstructive pulmonary disease. Trial registration: Current Controlled Trials ISRCTN14930255. Funding: This project was funded by the National Institute for Health Research (NIHR) Programme Grants for Applied Research programme and will be published in full in Programme Grants for Applied Research; Vol. 9, No. 13. See the NIHR Journals Library website for further project information.